GABA‐A receptor and mitochondrial TSPO signaling act in parallel to regulate melanocyte stem cell quiescence in larval zebrafish. (11th November 2019) - Allen, James R.; Skeath, James B.; Johnson, Stephen L.
Abstract: Tissue regeneration and homeostasis often require recruitment of undifferentiated precursors (adult stem cells; ASCs). While many ASCs continuously proliferate throughout the lifetime of an organism, others are recruited from a quiescent state to replenish their target tissue. A long‐standing question in stem cell biology concerns how long‐lived, non‐dividing ASCs regulate the transition between quiescence and proliferation. We study the melanocyte stem cell (MSC) to investigate the molecular pathways that regulate ASC quiescence. Our prior work indicated that GABA‐A receptor activation promotes MSC quiescence in larval zebrafish. Here, through pharmacological and genetic approaches we show that GABA‐A acts through calcium signaling to maintain MSC quiescence. Unexpectedly, we identified translocator protein (TSPO), a mitochondrial membrane‐associated protein that regulates mitochondrial function and metabolic homeostasis, as a parallel regulator of MSC quiescence. We found that both TSPO‐specific ligands and induction of gluconeogenesis likely act in the same pathway to promote MSC activation and melanocyte production in larval zebrafish. In contrast, TSPO and gluconeogenesis appear to act in parallel to GABA‐A receptor signaling to regulate MSC quiescence and vertebrate pigment patterning.